2016
DOI: 10.1021/acs.jpcb.6b00409
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid Dynamics Measured with 2D IR and IR Pump–Probe Experiments on a Linear Anion and the Influence of Potassium Cations

Abstract: The room-temperature ionic liquid EmimNTf2 (1-ethyl-3-methylimidazolium bis­(trifluoromethylsulfonyl)­imide) was studied with two-dimensional infrared (2D IR) spectroscopy and polarization selective pump–probe (PSPP) experiments using low-concentration selenocyanate (SeCN–) as the vibrational probe. SeCN– was added as EmimSeCN, which keeps the cation the same. KSeCN was also used, so K+ was added. Two 2D IR polarization configurations were employed: ⟨XXXX⟩ (all pulses have the same polarization) and ⟨XXYY⟩ (th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
81
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(94 citation statements)
references
References 62 publications
12
81
1
Order By: Relevance
“…This model has had great success in fitting 2D IR data for a variety of systems including organic liquids, water, proteins, liquid crystals, and room-temperature ionic liquids. [55][56][57][58][59][71][72][73][74][75] The multiexponential model was chosen as our starting point, as above T m , these glass forming liquids are simple organic liquids. At these higher temperatures, the CLS(T w ) decay curves for all three samples fit well to biexponential decays.…”
Section: Fitting Procedures and Choice Of Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…This model has had great success in fitting 2D IR data for a variety of systems including organic liquids, water, proteins, liquid crystals, and room-temperature ionic liquids. [55][56][57][58][59][71][72][73][74][75] The multiexponential model was chosen as our starting point, as above T m , these glass forming liquids are simple organic liquids. At these higher temperatures, the CLS(T w ) decay curves for all three samples fit well to biexponential decays.…”
Section: Fitting Procedures and Choice Of Modelmentioning
confidence: 99%
“…56 However, these power laws are not unique to simple glass forming liquids, and appear also in other complex liquids, such as liquid crystals and ionic liquids, 56,57,80,81 and are conspicuously absent from 2D IR experiments on these systems. [55][56][57][58] This highlights a fundamental difference in the spectral diffusion observable from other observables, in that relaxations that have complex functional forms in other techniques appear as simple exponential relaxations in 2D IR. While a full microscopic theory of spectral diffusion is lacking, it has been shown that schematic MCT correlators can describe the multi-exponential decay in liquid crystals 56 in the same way that they can describe the power law to exponential decay in OKE spectroscopy.…”
Section: Fitting Procedures and Choice Of Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Early MD simulations noted few linear hydrogen bonds with water 25 and many arrangements of dipolar character, while more recent MD simulations of SeCN -26 found an average of 3-4 hydrogen bonds, with one of them being an axial (linear) hydrogen bond. Ultrafast infrared spectroscopy has used the ν 3 mode of pseudo-halide anions to investigate ultrafast vibrational dynamics of water and other polar solvents, 23,[27][28][29][30][31][32] concentrated ion solutions, [33][34][35] ILs, [36][37][38][39][40] supported IL membranes, 41 and colloid emulsions. 42 Furthermore, a combination of MD simulations and ultrafast infrared spectroscopy developed a spectroscopic map of SeCNin D 2 O that describes the frequency dependence of the nitrile stretch to a hydrogen bonding environment.…”
Section: Introductionmentioning
confidence: 99%
“…24 Early MD simulations noted few linear hydrogen bonds with water 25 and many arrangements of dipolar character, while more recent MD simulations of SeCN -26 found an average of 3-4 hydrogen bonds, with one of them being an axial (linear) hydrogen bond. Ultrafast infrared spectroscopy has used the ν 3 mode of pseudo-halide anions to investigate ultrafast vibrational dynamics of water and other polar solvents, 23,[27][28][29][30][31][32] concentrated ion solutions, [33][34][35] ILs, [36][37][38][39][40] supported IL membranes, 41 and colloid emulsions. 42 Furthermore, a combination of MD simulations and ultrafast infrared spectroscopy developed a spectroscopic map of SeCNin D 2 O that describes the frequency dependence of the nitrile stretch to a hydrogen bonding environment.…”
Section: Introductionmentioning
confidence: 99%